2019
DOI: 10.1016/j.clnu.2018.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary omega-3 fatty acids on bones of healthy mice

Abstract: Subtle differences were noted at the bones' microstructural level, however these are likely the result of random effects that do not translate into changes that are biologically relevant. Similarly, differences were not seen at the mechanical level, nor were they reflected in blood-based biomarkers of bone metabolism. Altogether, dietary consumption of PUFA do not seem to affect bone structure or metabolism in a healthy model of growing mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…These findings demonstrated that the effect of n-3 PUFA on skeletal metabolism is also dependent on the type of n-3 FA ( Kruger and Schollum, 2005 ). On the other hand, Anez-Bustillos et al. (2018) did not observe any differences in tibia microstructural and blood-based biomarkers of bone metabolism in 3-wk old mice of both sexes fed diets supplemented with soybean oil (DHA, 8.4 g/kg) and DHA with arachidonic acid at a 20:1 ratio (DHA: arachidonic acid).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…These findings demonstrated that the effect of n-3 PUFA on skeletal metabolism is also dependent on the type of n-3 FA ( Kruger and Schollum, 2005 ). On the other hand, Anez-Bustillos et al. (2018) did not observe any differences in tibia microstructural and blood-based biomarkers of bone metabolism in 3-wk old mice of both sexes fed diets supplemented with soybean oil (DHA, 8.4 g/kg) and DHA with arachidonic acid at a 20:1 ratio (DHA: arachidonic acid).…”
Section: Discussionmentioning
confidence: 78%
“…(2018) did not observe any differences in tibia microstructural and blood-based biomarkers of bone metabolism in 3-wk old mice of both sexes fed diets supplemented with soybean oil (DHA, 8.4 g/kg) and DHA with arachidonic acid at a 20:1 ratio (DHA: arachidonic acid). It has been suggested that the potential effect of dietary n-3 PUFA may be more evident in the presence of disease ( Anez-Bustillos et al., 2018 ). The discrepancies in the results might be related to the various factors including type, dose, and duration of the intervention ( Rajaram et al., 2017 ) and to the target population, which included the presence of disease or provoked immune response ( Anez-Bustillos et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the bone attributes were not normalized based on the BW ( Korotkova et al., 2005 ). These differences in the results might be related to various factors including the type of FA ( Kruger and Schollum, 2005 ), FA dosage ( Kruger and Schollum, 2005 ), duration of intervention ( Cohen and Ward, 2005 ), and the health status of target population ( Anez-Bustillos et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…A positive effect of seeds, flax oil, soybean oil, sunflower oil, sesame oil, and olive oil on bone tissue has been demonstrated [ 9 , 10 , 11 , 12 , 13 , 14 ]. However, there are also studies indicating a controversial impact of these oils [ 12 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%